Repeat liver resection after a hepatic or extended hepatic trisectionectomy for colorectal liver metastasis. Issue 3 (22nd July 2013) - Ziff, Oliver; Rajput, Ibrahim; Adair, Robert; Toogood, Giles J.; Prasad, K. Rajendra; Lodge, J. Peter A.
Abstract Objective A right and left hepatic trisectionectomy and an extended trisectionectomy are the largest liver resections performed for malignancy. This report analyses a series of 23 patients who had at least one repeat resection after a hepatic trisectionectomy for colorectal liver metastasis (CRLM). Methods A retrospective analysis of a single‐centre prospective liver resection database from May 1996 to April 2009 was used for patient identification. Full notes, radiology and patient reviews were analysed for a variety of factors with respect to survival. Results Twenty‐three patients underwent up to 3 repeat hepatic resections after 20 right and 3 left hepatic trisectionectomies. In 18 patients the initial surgery was an extended trisectionectomy. Overall 1‐, 3‐ and 5‐year survival rates after a repeat resection were 100%, 46% and 32%, respectively. No factors predictive for survival were identified. Conclusion A repeat resection after a hepatic trisectionectomy for CRLM can offer extended survival and should be considered where appropriate.